Assessing the Role of Training Needs, Resources, and Perceptions in Enhancing Employee Performance - Tabita, I Dewa Ayu Tita Permata; Gayatri, I Gusti Agung Sasih (JUSTBEST Journal of Sustainable Business and Management, 2024)
This study aims to analyze the effect of Training Needs Assessment (TNA) , Training Resource Availability (TRA), and Employee Perception Towards Training (EPT) on Employee Performance at PT. HARMONI PERMATA. The problems faced by the company are the mismatch between the training provided and the needs of employee work, as well as the limited resources that support the training. In addition, employee perceptions of training also affect the effectiveness of the program. This study uses a quantitative approach with a descriptive and explanatory design, involving 30 employee respondents who have participated in training. Data were collected through questionnaires that measured the three variables studied, and analyzed using multiple linear regression analysis. The results showed that all three variables had a significant effect on employee performance. Employee Perception Towards Training (EPT) gave the most significant effect with a regression coefficient of 0.50, followed by Training Needs Assessment (TNA) with a coefficient of 0.45, and Training Resource Availability (TRA) with a coefficient of 0.30. These findings indicate that training designed with employee needs in mind, supported by adequate resources, and received with positive perceptions can significantly improve employee performance.